Muted Group in Algorithms : A Comparative Study of ‘Janda’ (Widow) Stigmatisation and ‘Duda’ (Widower) Glorification on Google Trends - Chania, Silmy; Andayani, Marisa; Irwansyah, Irwansyah (Journal of Content and Engagement, 2026)
Digital transformation in Indonesia does not necessarily dismantle patriarchal cultural structures but instead replicates them within cyberspace. Digital footprints on search engines reflect deep-seated gender biases, where post-separation marital status is interpreted unevenly between men and women. This study aims to compare the search patterns of the keywords 'Janda' and 'Duda' on Google Trends Indonesia and to uncover the muting mechanisms operating within search algorithms using the perspective of Muted Group Theory. This research employs a descriptive qualitative approach with data mining techniques on the Related Queries feature over the last 12 months. Data were analyzed using Qualitative Content Analysis through the stages of immersion, coding, and thematic categorization. Research findings show extreme semantic disparities. The keyword 'Janda' is dominated by themes of stigmatisation, sexuality, and the commodification of gambling, indicating the mechanisms of Ridicule and Control at work. Conversely, the keyword 'Duda' is dominated by themes of popular culture glorification (duda wattpad) and positive socio-economic status attribution (duda kaya / wealthy widower), showing Semantic Elevation. This study concludes that algorithms act as active agents that amplify gender bias, placing women in the position of a muted group while men remain in control as dominant subjects in digital narratives.